Carboxymethyl cellulose formulation of a South African isolate of Steinernema yirgalemense: CMC for the culture of S. yirgalemense - Malan, Antoinette Paula; Schlesinger, Subriena; Dunn, Murray (South African Journal of Enology and Viticulture, 2026)
The South African organic wine production is a small but rapidly growing sector supported by increasing global demand for organic wines. In growing organic vines, the process relies on the use of approved products available for organic production. At the same time in table grapes, entomopathogenic nematodes (EPNs) offers and excellent solution for managing key insect pests, particularly by addressing challenges related to maximum residue limits and with the with-holding period before and during the harvesting of grapes intended for export. Research on the use of EPNs in South Africa has demonstrated their potential as effective biological control agents against major grapevine pests, including the vine mealybug, false codling moth and the banded fruit weevil. Key to their commercial success is the development of a formulation protocol for the active ingredient, which are the infective juveniles (IJ) nematodes, which possesses prolonged shelf-life, without negatively affecting their pathogenicity and application methods. This study assessed the shelf-life and pathogenicity of a carboxymethyl cellulose (CMC)-based formulation, using a South African isolate, Steinernema yirgalemense 157-C. The infective IJs used in this study, were cultured by means of in vitro liquid culture in Erlenmeyer flasks. The results showed that at 14°C, with a 5% CMC concentration, offered the highest viability of 79%, over a period of 21 days with no negative effect on the infection potential of the IJs.